Allegories of Love : Cervantes's Persiles and Sigismunda - Wilson, Diana de Armas, 1934- (Book collections on Project MUSE., 1991)
In the work he considered his masterpiece, Persiles and Sigismunda, Cervantes finally explores the reality of woman--an abstraction largely idealized in his earlier writing. Traditional critics have perpetuated this disembodied ideal woman: ""Every Man, "" claimed the translators of the 1706 Don Quixote, has ""some darling Dulcinea of his Thoughts."" As Diana de Armas Wilson shows, however, Cervantes himself envisioned the radical embodiment of ""Dulcinea"" in the later Persiles, a pan-European Renaissance allegory. Wilson illuminates Cervantes's strategic use of the ancient genre of Greek r